Analisis Klausa Dalam Kalimat Majemuk Pada Novel Wedding Agreement Bab Bukan Pernikahan Impian Karya Mia Chuz : Sebuah Kajian Sintaksis - Santi Rusmayanti; Iis Ristiani (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to analyze clauses in compound sentences in Mia Chuz's Wedding Agreement Novel. The research method used is qualitative descriptive research method. The descriptive method is the presentation of data based on facts as contained in the novel